Integrating Geospatial Technology and Islamic Jurisprudence: An Analysis of Qibla Deviation in Mosques - Reno Ismanto; Ahmad Fadholi; Priyanggo Karunia Rahman; Sahibzada Muhammad Waseem Jan; Hasna Tuddar Putri (Universitas Islam Sultan Agung, 2026)
Purpose - Accurate orientation towards the qibla is a fundamental requirement for the validity of prayer in Islam. However, many mosques, particularly those constructed in earlier periods, may exhibit discrepancies in their qibla orientation due to the limited technology and directional methods available at the time of construction. Previous studies on qibla direction have generally focused on technical and astronomical aspects, while integrative studies combining geospatial analysis with Islamic jurisprudence (fiqh) evaluation remain limited. Recent developments in geospatial technology and digital astronomy provide new opportunities to reassess qibla accuracy with greater precision, while also necessitating normative evaluation from the perspective of Islamic law. This study aims to analyse the degree of qibla deviation in mosques in Pangkalpinang City, Indonesia, and to examine its legal implications based on relevant fiqh principles.Methodology/approach - The research employs an empirical-normative approach. Empirical data were collected through field measurements using Islamic Astro, GPS Test, Google Earth Pro, and Istiwaaini applications, as well as solar-position tracking to obtain highly accurate coordinate and qibla azimuth data. The results were then compared with the physical orientation of the mosque buildings. The normative analysis was conducted by examining fiqh perspectives regarding the acceptable tolerance limits for qibla deviation.Findings - The findings reveal that the qibla deviations of the twelve surveyed mosques range from 0.54° to 38.63°, indicating that several mosques do not fully meet the tolerance standards recognised in fiqh.Conclusion - The integration of modern geospatial technology with Islamic legal analysis provides a more comprehensive framework for evaluating mosque qibla accuracy, while encouraging higher precision through modern scientific verification. This study contributes to the development of science-based fiqh studies of worship and reaffirms the relevance of the principle of easing hardship for legally responsible persons (at-taysīr 'alā al-mukallaf) in the context of technological advancement. Furthermore, the study recommends that religious authorities and mosque administrators verify qibla orientation using scientific approaches that remain consistent with sharia principles in order to ensure confidence and stability in worship.